The Genetic and Epigenetic Journey of Embryonic Stem Cells into Mature Neural Cells - Olynik, Brendan; Rastegar, Mojgan (Frontiers in Genetics, 2012)
Epigenetic changes occur throughout life from embryonic development into adulthood. This results in the timely expression of developmentally important genes, determining the morphology and identity of different cell types and tissues within the body. Epigenetics regulate gene expression and cellular morphology through multiple mechanisms without alteration in the underlying DNA sequences. Different epigenetic mechanisms include chromatin condensation, post-translational modification of histone proteins, DNA cytosine marks, and the activity of non-coding RNA molecules. Epigenetics play key roles in development, stem cell differentiation, and have high impact in human disease. In this review, we will discuss our current knowledge about these epigenetic mechanisms, with a focus on histone and DNA marks. We will then talk about the genetics and epigenetics of embryonic stem cell self-renewal and differentiation into neural stem cells, and further into specific neuronal cell types.